Genetically distinct pestiviruses pave the way to improved classical swine fever marker vaccine candidates based on the chimeric pestivirus concept. Issue 1 (1st January 2020) - Postel, Alexander; Becher, Paul
ABSTRACT: Classical swine fever (CSF) is one of the most important viral diseases of pigs. In many countries, the use of vaccines is restricted due to limitations of subunit vaccines with regard to efficacy and onset of protection as well as failure of live vaccines to d ifferentiate i nfected from v accinated a nimals (DIVA principle). Chimeric pestiviruses based on CSF virus (CSFV) and the related bovine viral diarrhea virus (BVDV) have been licensed as live marker vaccines in Europe and Asia, but cross-reactive antibodies can cause problems in DIVA application due to close antigenic relationship. To develop marker vaccine candidates with improved DIVA properties, three chimeric viruses were generated by replacing E rns of CSFV Alfort-Tübingen with homologue proteins of only distantly related pestiviruses. The chimeric viruses "Ra", "Pro", and "RaPro" contained E rns sequences of Norway rat and Pronghorn pestiviruses or a combination of both, respectively. In porcine cells, the "Pro" chimera replicated to high titers, while replication of the "Ra" chimera was limited. The "RaPro" chimera showed an intermediate phenotype. All vaccine candidates were attenuated in a vaccination/ challenge trial in pigs, but to different extents. Inoculation induced moderate to high levels of neutralizing antibodies that protected against infection with a genetically heterologous, highly virulent CSFV. Importantly, serum samples of vaccinated animals did not show any cross-reactivity in a CSFV E rns antibody ELISA. In conclusion, the E rns antigen from distantly related pestiviruses can provide a robust serological negative marker for a new generation of improved CSFV marker vaccines based on the chimeric pestivirus concept.